LOWWALL SLOPE STABILITY OF PANEL 32 AND PANEL 36 PT. XYZ, SOUTH KALIMANTAN - Jamil, Aliyuddin; Sophian, Raden Irvan; Rendra, Pradnya Paramarta Raditya (Journal of Geological Sciences and Applied Geology, 2023)
The research was conducted in the coal mining area of PT. XYZ, South Kalimantan. The research aims to create a geological model for each cross-section according to the characteristics of materials and to calculate the slope stability of the lowwall slope. The researcher calculated the slope stability using Morgenstern-Price method with Rocscience Slide2 software. The geological conditions of the study area are composed of alternating sandstones with coal-inserted claystone and coal-inserted claystone from the Warukin Formation. Material properties at the study area are composed of sandstone, claystone, and coal. The results of the slope stability simulation show that the lowwall panel 32 slope has a safety factor value of 1.081 while the lowwall panel 36 slope has a safety factor value of 1.107.